RAD52 and ERCC6L/PICH have a compensatory relationship for genome stability in mitosis. - Beth Osia; Arianna Merkell; Felicia Wednesday Lopezcolorado; Xiaoli Ping; Jeremy M Stark (PLoS Genetics)
Mammalian RAD52 is a DNA repair factor with strand annealing and recombination mediator activities that appear important in both interphase and mitotic cells. Nonetheless, RAD52 is dispensable for cell viability. To query RAD52 synthetic lethal relationships, we performed genome-wide CRISPR knock-out screens and identified hundreds of candidate synthetic lethal interactions. We then performed secondary screening and identified genes for which depletion causes reduced viability and elevated genome instability (increased 53BP1 nuclear foci) in RAD52-deficient cells. One such factor was ERCC6L, which marks DNA bridges during anaphase, and hence is important for genome stability in mitosis. Thus, we investigated the functional interrelationship between RAD52 and ERCC6L. We found that RAD52 deficiency increases ERCC6L-coated anaphase ultrafine bridges, and that ERCC6L depletion causes elevated RAD52 foci in prometaphase and interphase cells. These effects were enhanced with replication stress (i.e. hydroxyurea) and topoisomerase IIα inhibition (ICRF-193), where post-treatment effect timings were consistent with defects in addressing stress in mitosis. Altogether, we suggest that RAD52 and ERCC6L co-compensate to protect genome stability in mitosis.